Is the Renminbi a Global Currency in the Making? Globalization of Digital yuan - Wycliffe Obwori, Alwago (Public Finance Quarterly, 2022)
Since the global financial recession of 2008 and the subsequent sovereign debt crisis, the US economic supremacy has experienced setbacks. China has steadily grown into a dependable economic force across the globe, particularly in Asia. Is the renminbi on the verge of becoming a global currency given the financial domination setbacks of the US economy? In this critical review analysis, I contend that the dollar’s hegemonic position is at risk, but the political and economic climate does not appear to be ripe for renminbi globalization. The Chinese hawks see the economic sanctions levied against Russia following the Ukraine invasion as a chance to challenge the dominance of the US dollar. Furthermore, China has benefited from the first-mover advantage through the launching of the Central Bank Digital Currency. However, China must gain the trust of foreign users in the robustness of its financial system, economy, and digital yuan’s functionality for the globalization of the digital yuan to be effective. Moreover, to promote renminbi internalization, China must ease capital regulations, increase renminbi convertibility, and restructure its financial system.